Revolutionizing the family : politics, love, and divorce in urban and rural China, 1949-1968 - Diamant, Neil J., 1964- (University of California Press, 2000)
In contrast to previous studies of the Marriage Law in China between 1949 and 1968, this text argues that the law reshaped marriage and family relationships in significant - but often unintended - ways throughout the Maoist period.